PKM KERAJINAN INU DAN KERUPUK SAGU DASA WISMA MELATI 2 SIBERUT SELATAN KEPULAUAN MENTAWAI - Alfattory Rheza Syahrul; Kaksim Kaksim; Jimi Ronald (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2019)
The main issues in this service are related to sales and attractiveness and understanding related to product promotion. As well as the basis for using online applications, e-Commerce implementation requires a fundamental paradigm shift, from the original marketplace that emphasizes physical interaction between sellers and buyers into a market space that relies on electronic transactions. In a traditional marketplace, information, product / service, and payment traffic is physical (location based). In other words, the applicable business model is the geographic business model. Conversely, in a virtual marketplace, product information flow, communication processes between producers and consumers, distribution of goods / services and transactions take place in a virtual / virtual world. The purpose of this service is to improve the production process and the process of selling and utilizing resources in activities and choosing the right marketing channels as well as in the use of media so that the Jasmine 2 group in Batjoja Hamlet is one of the business actors that produce local processed products in Siberut District South. These service methods are outreach, activity assistance, attractive product packaging, online marketing management and activity evaluation. The result of this dedication is that the effort is socialized in this service through social media such as IG, and BUKALAPAK https://www.bukalapak.com/u/craftsinukerupuksagu. Brands and packaging have been designed in such a way and are expected to be increasingly recognized, the Service Team has also provided debriefing to partners in the form of "Smart Packaging" through training and outreach on suitable and appropriate packaging in attracting prospective customers, "standing poch" packaging with seals, which is more flexible and attractive in various sizes. The packaging is ready to be affixed to a complete brand sticker with the label. And many orders have arrived, especially from outside the Mentawai Islands district. Conclusion Melati 2 Group in running a business has the potential to produce value and money. Although the sales of the products produced namely inu craft and sago crackers are getting better locally but the equal distribution of sales and marketing of products is very good and many are interested, but it's just that the potential for promotion must always be done, especially for marketing outside the Island or outside the Regency so that in improving the economic partner groups in particular will increasingly step up. This is also based on information and education held by partner groups in terms of the production process and marketing selection